Use of salicylic acid as an attenuator to the effects of water deficit on basil plants / Uso do ácido salicílico como atenuador aos efeitos do déficit hídrico em plantas de manjericão - Josabete Salgueiro Bezerra de Carvalho; João Pedro Ramos da Silva; Rita de Cássia Monteiro Batista (Universidade Estadual de Alagoas, 2020)
n recent years the water availability has been strongly affected by generating negative impacts on plants. Mechanisms that allow the plants to resist prolonged periods of drought have been a strategy for maintenance of agricultural production. With this, the aim of this work was to evaluate the use of salicylic acid as a strategy to mitigate the effects of water deficit on plants of Basil (Ocimum basilicumL.). The treatments consisted of: T1-irrigated Plantswithout the application; T2-Plants irrigated with the application; T3-non-irrigated Plants without the application; and T4-plants irrigated with the application. In relation to the Visual symptoms, salicylic acid dampen the wilting of plants not irrigated, not interfering too at the time of Basil plants. Regarding stomatal conductance, there was an increase of over 100% for non-irrigated plants with (T4) when compared to non-irrigated plants without the (T3). For the leaf temperature, the water deficit influenced the increase in temperature. In relation to the relative content of water there has been an increase of 44.5% with application of the plants not irrigated (T4) compared with non-irrigated plants without the (T3). In relation to the relative contentof water there has been an increase of 44.5% with application of the plants not irrigated (T4) compared with non-irrigated plants without the (T3). We concluded that the salicylic acid contributed positively as buffer the effects of water stress on Basilplants, promoting an increase in stomatal conductance and relative water content.